BMC Immunology - Aronin, Tovah; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Immunology is an open access journal publishing original peer-reviewed research articles in molecular, cellular, tissue-level, organismal, functional, and developmental aspects of the immune system as well as clinical studies and animal models of human diseases. Topics include: Allergy and hypersensitivity Cellular immunology and immune regulation Clinical immunology: transplants, autoimmunity, immunodeficiency and vaccines Immunity to infection and tumors Immunogenetics, immunogenomics and systems immunology Innate immunity and inflammation As a BMC Series journal, BMC Immunology does not make editorial decisions based on the perceived interest or potential impact of a study. Manuscripts are considered for publication if they are scientifically valid. For research articles, this includes having a clearly defined and sound research question, appropriate methodology and analysis, and adherence to community-agreed standards relevant to the field.
Keywords: Immunology; Allergy; Pharmacology; Cytokines; Immunology; Allergology; Pharmacology; Cytokines and Growth Factors